Resting-state functional connectivity correlates of anxiety co-morbidity in major depressive disorder. (July 2022) - Briley, PM; Webster, L.; Boutry, C.; Cottam, WJ; Auer, DP; Liddle, PF; Morriss, R.
Abstract: Major depressive disorder (MDD) is frequently co-morbid with anxiety disorders. The co-morbid state has poorer functional outcomes and greater resistance to first line treatments, highlighting the need for novel treatment targets. This systematic review examined differences in resting-state brain connectivity associated with anxiety comorbidity in young- and middle-aged adults with MDD, with the aim of identifying novel targets for neuromodulation treatments, as these treatments are thought to work partly by altering dysfunctional connectivity pathways. Twenty-one studies met inclusion criteria, including a total of 1292 people with MDD. Only two studies included people with MDD and formally diagnosed co-morbid anxiety disorders; the remainder included people with MDD with dimensional anxiety measurement. The quality of most studies was judged as fair. Results were heterogeneous, partly due to a focus on a small set of connectivity relationships within individual studies. There was evidence for dysconnectivity between the amygdala and other brain networks in co-morbid anxiety, and an indication that abnormalities of default mode network connectivity may play an underappreciated role in this condition. Highlights: Systematic review of brain connectivity correlates of anxiety in major depression. Includes twenty-one studies of fMRI functional or effective connectivity. Findings suggest amygdala dysconnectivity with increasing anxiety. Reduced amygdala regulation from executive control and default mode networks. Default mode network areas may represent novel targets for neuromodulation.